A problem of budget rigidities in the state budget and the evolving environment of Polish public finances - Michał Ostrowski (Prawo Budżetowe Państwa i Samorządu)
This article deals with a problem of budget rigidities. At the outset, the doctrinal definitions of budged rigidities were cited and analyzed. On this basis, the Author developed a catalogue of rigidities, the elements of which were later classified into appropriate expenditure groups. In the further part of the work, methods of making ridged expenses more flexible are presented. Then, the problem of an excessive increase in budged rigidities is presented in the context of the marginalization of the state budget process that has been progressing in recent years. On the basis of the current processes taking place in the fiscal policy, the author indicates the need to consider the described problem in a wider context.